(untitled) (Eurasian Journal of Physics,Chemistry and Mathematics, 2022)
In this article, a new method for finding the solution of an integro-differential equation involving a fractional operator is proposed, with the help of which solutions of homogeneous and non-homogeneous equations are found. This method is based on the construction of a normal system of functions with respect to the fractional integro-differential operator.